Feminism and Its Associations with Weight Stigma, Body Image, and Disordered Eating: A Risk or Protective Factor? - Brooke L. Bennett; Allison F. Wagner; Rebecca M. Puhl; Alexis Lamere; Janet D. Latner (Obesities)
The feminist perspective is relevant to the understanding, prevention, and treatment of disturbances in eating and body image. However, limited empirical research has explored the relationship between feminist identity and weight stigma. The present study examined the associations between feminist beliefs, externalized weight bias, internalized weight bias, body image, and eating disturbances. Two hundred sixty-five racially and ethnically diverse young women were recruited from a university in the Pacific Rim. Participants completed questionnaires online and interrelationships were examined using a series of regressions. Externalized weight bias was significantly negatively associated with both feminist beliefs and identification as a feminist. However, stronger feminist beliefs and identity were significantly associated with higher internalized weight bias, worse body dissatisfaction, and greater incidence of eating disturbances. The results of the present study suggest that structural change driven by feminist values and principles may be effective for reducing weight bias and possibly other risk factors present in broader society but potentially less effective on an individual level. Longitudinal research is needed to confirm the direction of these relationships and to understand which components of feminist theory and feminist values can be most helpful in reducing weight bias on an individual level, while still addressing structural change.